2001
DOI: 10.1063/1.1365958
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic diffusion of energetic ions in optimized stellarators

Abstract: It is shown that the collisionless transformation of locally trapped and passing particle orbits in the optimized stellarators of the Wendelstein line results in stochastic diffusion of energetic ions. This diffusion can lead to the loss of a significant fraction of the energetic ion population from the region where the characteristic diffusion time is small compared to the slowing down time. The loss region and losses can be minimized by shaping the plasma temperature and density profiles so that they satisfy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 13 publications
3
78
0
Order By: Relevance
“…A blocked particle's trajectory is not restricted to a single toroidal segment but extends to neighbouring sections. Such particles are also called transitioning [2]. An illustration of these three types of orbits and a comparison with particle orbits in an axisymmetric plasma is given in Fig.…”
Section: Localised or Toroidally Trapped Particlesmentioning
confidence: 99%
See 2 more Smart Citations
“…A blocked particle's trajectory is not restricted to a single toroidal segment but extends to neighbouring sections. Such particles are also called transitioning [2]. An illustration of these three types of orbits and a comparison with particle orbits in an axisymmetric plasma is given in Fig.…”
Section: Localised or Toroidally Trapped Particlesmentioning
confidence: 99%
“…Stochastic diffusion of fast ions in optimised stellarators has been described in [2]. This diffusion process concerns transitioning particles, described in 3.…”
Section: Loss Channels 41 Stochastic Diffusion Lossesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it turned out that a considerable fraction of particles are still lost before their thermalization, the main reason of the loss being the stochastic diffusion (SD), i.e., the collisionless diffusion occurring because of the stochastization of the particle motion. Later it was shown that the most important mechanism of the SD in Wendelstein-type configurations, which dominates the particle loss, is the diffusion of the transitioning particles due to radial jumps during the transitions between the locally trapped and locally passing states [14]. This diffusion is similar to the diffusion of charged particles due to repeated trapping and detrapping in a wave with varying amplitude; it was earlier considered for the particles transitioning between the locally trapped and toroidally trapped states in a tokamak with toroidal field ripple (see [15] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The stochastic diffusion (SD) resulting from collisionless transformations between locally trapped and locally passing orbits may lead to a significant loss of energetic particles from stellarator plasmas (Beidler C D et al 2001 Phys. Plasmas 8 2731.…”
mentioning
confidence: 99%